Penerapan Pembelajaran Berbasis Proyek dan Hasil Belajar Mahasiswa - Andy Amir; Adila Solida (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The application of traditional learning methods has not shown a significant increase in learning outcomes in terms of critical thinking, scientific attitudes and communication skills. Students need innovative learning that can improve learning outcomes. The purpose of this study was to measure the increase in student learning outcomes between before and after implementing the project-based learning model (PjB).This research is a quantitative study with a quasi-experimental design. The number of respondents was 36 students of the fifth semester of the Jambi University Public Health Sciences Study Program. The instrument used is an assessment sheet before (pre-test) and an assessment sheet after (post-test) the experiment. Measurement of improvement in learning outcomes includes aspects of critical thinking, scientific attitude and communication skills. Data collection was carried out twice in the pre-test and post-test. Data processing using statistical software. Data analysis was carried out through the univariate and bivariate analysis stages using the T test. The results showed that there were differences in student learning outcomes between before and after applying the project-based learning model (PjB) on aspects of communication skills, critical thinking and learning achievement. The application of project-based learning contributes to improving student learning outcomes who are able to think critically, have a scientific attitude and are skilled in communication. So it is recommended that every subject in higher education use this learning method which makes students actively involved in complex learning processes.